CYP3A5 genotype has a dose-dependent effect on ABT-773 plasma levels - Katz, David A; Grimm, David R; Cassar, Steven C; Gentile, Maria C; Ye, Xin; Rieser, Matthew J; Gordon, Eric F; Polzin, Jill E; Gustavson, Linda E; Driscoll, Rita M; O'dea, Robert F; Williams, Laura A; et al. (Clinical pharmacology and therapeutics, 2004)
The metabolizing enzyme cytochrome P450 (CYP) 3A5 is polymorphically expressed as a result of genetic variants that do not encode functional protein. Because of overlapping substrate specificity with CYP3A4 and the multidrug efflux pump P-glycoprotein, the importance of CYP3A5 genetic polymorphism for pharmacokinetics is controversial. Our objective was to determine whether genetic polymorphisms in CYP3A5 or MDR-1 (which encodes P-glycoprotein) influence the drug levels of ABT-773, a ketolide antibiotic that is a substrate for both CYP3A and P-glycoprotein. Healthy volunteers given 3 different oral dose levels of ABT-773 were genotyped at 2 common CYP3A5 and 7 common MDR-1 polymorphisms. Individuals were categorized as CYP3A5-positive if they carried at least 1 functional CYP3A5*1 allele and as CYP3A5-negative if they did not. Area under the plasma concentration-time curves (AUCs) from 0 to 6 hours (AUC(t)) and maximum postdose plasma concentration (C(max)) after a single dose and on day 5 of a twice-daily regimen were calculated and correlated with genotypes. ABT-773 AUC(t) and C(max) were, on average, higher in CYP3A5-negative subjects given 450 mg ABT-773 (n = 9) than in CYP3A5-positive subjects with identical doses (n = 8). The relationship for AUC(t) was statistically significant both after a single dose (geometric mean and 95% confidence interval [CI], 5.0 microg.h/mL [3.9-6.4 microg.h/mL] versus 2.8 microg.h/mL [1.8-4.3 microg.h/mL]; P =.03) and on the fifth day of twice-daily dosing (12.4 microg.h/mL [8.7-17.6 microg.h/mL] versus 7.4 microg.h/mL [5.5-9.8 microg.h/mL], P =.04). The relationship for C(max) was statistically significant after a single dose (1220 microg/mL [867-1167 microg/mL] versus 727 microg/mL [506-1044 microg/mL], P =.04) and showed a trend in the same direction on the fifth day of twice-daily dosing (2566 microg/mL [1813-3631 microg/mL] versus 1621 microg/mL [1122-2343 microg/mL], P =.07). In contrast, AUC(t) and C(max) were not significantly different between CYP3A5-positive and CYP3A5-negative individuals given 150 mg or 300 mg ABT-773. ABT-773 plasma levels did not trend with MDR-1 genotypes. These results suggest that CYP3A5 genotype may be an important determinant of in vivo drug disposition and that this effect may be dose-dependent.